(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This study examines the mechanisms for enhancing the investment activity of joint-stock companies based on the experience of developed countries. The research focuses on the theoretical foundations and practical approaches to investment activity, highlighting the role of financial markets, institutional investors, and corporate governance systems in facilitating capital formation. A comparative analysis of the United States, Germany, and Japan is conducted to identify the key features of different financial models, including market-based, bank-based, and hybrid systems. The findings indicate that the level of investment activity in developed economies is largely determined by the depth of financial markets, the presence of institutional investors, and the effectiveness of corporate governance practices. In particular, the study reveals that stock market development and access to diverse financial instruments significantly enhance the ability of joint-stock companies to attract investment. Furthermore, the research emphasizes the importance of a stable institutional environment and transparent regulatory framework in promoting investor confidence.